PEMAHAMAN ORANG TUA TERHADAP KONSEP DASAR PENDIDIKAN ANAK USIA DINI DI KECAMATAN SENGAH TEMILA - Ratnasari, Wesi; Yuniarni, Desni; Lukmanulhakim, Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to describe the level of understanding of parents towards the basic concept of ECD in Sengah Temila District. The research method used is quantitative, with the form of survey research, data analysis using descriptive statistics. Data is collected by indirect communication techniques and data collection tools in the form of questionnaires. The sample used was 99 respondents. The results of the study show (1). parents' understanding of the notion of ECD 92% is categorized as "very understanding", (2). parents' understanding of the purpose of PAUD 54% enter the category "very understanding", (3). parents' understanding of the function of PAUD 93% entered the category "very understanding", (4). parents' understanding of ECD learning 92% enter the category of "very well-informed", (5). parents' understanding of the PAUD curriculum 83% enter the category of "very understanding", (6). parents' understanding of the role of parents in PAUD 86% enter the category of "understand". So that it can be concluded that parents' understanding of the basic concept of PAUD in Sengah Temila Subdistrict is categorized as "very understanding". Suggestions for research by parents can be present at each school to hold a meeting, and parents can increase their understanding of the basic concepts of PAUD by learning things about PAUD through media, books, and parents.Keywords: Basic concepts of early childhood education, Parentes, Understanding